Drupacine as a potent SARS-CoV-2 replication inhibitor in vitro - Chen Yang; Yanying Yu; Qi Peng; Jingwei Song; Bo Sun; Yi Shi; Qiang Ding (Elsevier, 2024)
Despite the availability of vaccines and antiviral treatments, the continued emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and breakthrough infections underscores the need for new, potent antiviral therapies. In a previous study, we established a transcription and replication-competent SARS-CoV-2 virus-like particle (trVLP) system that recapitulates the complete viral life cycle. In this study, we combined high-content screening (HCS) with the SARS-CoV-2 trVLP cell culture system, providing a powerful phenotype-oriented approach to assess the antiviral potential of compounds on a large scale. We screened a library of 3,200 natural compounds and identified drupacine as a potential candidate against SARS-CoV-2 infection. Furthermore, we utilized a SARS-CoV-2 replicon system to demonstrate that drupacine could inhibit viral genome transcription and replication. However, in vitro, enzymatic assays revealed that the inhibition could not be attributed to conventional antiviral targets, such as the viral non-structural proteins nsp5 (MPro) or nsp12 (RdRp). In conclusion, our findings position drupacine as a promising antiviral candidate against SARS-CoV-2, providing a novel scaffold for developing anti-coronavirus disease 2019 therapeutics. Further investigation is required to pinpoint its precise target and mechanism of action.